Polyhydramnios as a sole ultrasonographic finding for detecting fetal hemolytic anemia caused by anti-c alloimmunization - Shih-Chung Wang; Yun-Chia Wu; Wan-Ju Wu; Mei-Hui Lee; Wen-Hsiang Lin; Gwo-Chin Ma; Ming Chen (Elsevier, 2022)
Objective: The prenatal course of a rare case with fetal anemia caused by maternal anti-c alloimmunization was reported. Case report: A 39-year-old female with anti-c and anti-E antibodies against red cells had previously experienced a stillbirth. At her present pregnancy, titers of maternal antibodies and fetal middle cerebral artery peak systolic velocity (MCA-PSV) were frequently monitored to investigate the severity of fetal hemolytic anemia. Rather than manifesting as an increase in MCA-PSV, the anemic fetus was delivered at 32 weeks and one day of gestation with a sole presentation: polyhydramnios. Neonatal hospitalization course were compatible with hemolytic anemia. The baby was discharged at 48 days of age. Conclusion: This case illustrated the complexities of dealing with maternal red cell alloimmunization during pregnancy and the limitations of noninvasive diagnostic modalities for detecting fetal anemia, and highlighted that obstetricians should refer all available clinical parameters in order to offer appropriate perinatal care.